Molecular Data Confirm The Presence Of Nycticebus Bengalensis On Langkawi Island, Malaysia - Badrul Munir Md-Zain; Khairul Sya’adah Mohhoyua; Nor Rahman Aifat; Norshaqinah Ayob; Jeffrine Japning Rovie-Ryan; Ahmad Ampeng; Abd Rahman Mohd-Ridwan; Mary E Blair; Muhammad Abu Bakar Abdul-Latiff; Ehwan Ngadi (Society for Indonesian Biodiversity, 2024)
Volume: 20 No: 4